IMPLEMENTASI PERANGKAT IOT (INTERNET OF THINGS) SEBAGAI SISTEM PEMANTAU DAN PENGENDALI KENDARAAN - Petrus Sokibi; Ady Widjaja (Universitas Budi Luhur, 2018)
Motor vehicles are very vulnerable objects to be stolen. Anticipation of theft is not enough simply by installing a security lock such as a double-lock, but the vehicle can be equipped with a monitoring system and controller to provide more security level. Motor vehicles are generally not equipped with a GPS device, so need to be equipped with these devices and also embedded systems can be monitored remotely. The use of embedded systems is an option to be implemented because it is power-efficient and the price is relatively cheap using Raspberry Pi 3 Model B, GSM modem, Ublox 6M V2 GPS and DC relay as IoT device. The device comes with an application connected to the Initial State server and then mounted on the vehicle. When enabled, the IoT tool will transmit vehicle position data from GPS satellites to the Initial State server. The control function of this device also utilizes Telegram Bot which is planted on IoT device with the function of receiving commands from users via Telegram chat application to set the condition of relay module whether on or off, which becomes switch function between Engine Control Module to coil vehicle as electric current to start the machine. The result of the research is a vehicle monitoring and control device using Raspberry Pi, as the main module.